Reception, criticism and appropriation of the metaphysics in Hegel’s Science of Logic - Costa, Danilo Vaz-Curado R. M.; Pertille, José Pinheiro (Aufklärung: journal of philosophy, 2017)
The present analysis defends the thesis that Hegel elaborates an original transformation of the concept of metaphysics, assuming its presuppositions as they were developed in the philosophic tradition, that metaphysics is a doctrine of the first principles, a theory of Being, a theodicy and even, as for Kant, a theory of knowledge.